Evaluation of low-carbon benefits of smart grids based on a three-stage DEA model - Ying Chen; Shuqi Li; Siyao Lu; Lin Yang; Songhai Fan (2016 International Conference on Smart Grid and Clean Energy Technologies (ICSGCE), 2016)
As the national energy and environmental problems becomes more acute, an urgent subject that needs to be solved by power enterprises is to strengthen energy conservation and emission reduction as well as to improve low-carbon benefits. The existing literature has neither provided a complete system for evaluating the low-carbon benefits of smart grids, nor eliminated the influences of environmental constraints. This paper introduces a three-stage DEA model on the basis of eliminating the environmental factors and builds an evaluation system for low-carbon benefits in line with the characteristics of the national smart grids. Meanwhile, the low-carbon benefits of the regional smart grids in 2020 are estimated through public data, which presents a clear direction for scientific layout and development of the smart grids.